Object-oriented Oracle - Rahayu, Johanna Wenny. (CyberTech Pub., 2005)
"The book covers comprehensive and fundamental aspects of the implementation of object-oriented modeling in a DBMS that was originated as a pure Relational Database, Oracle"--Provided by publisher.